Faith and Spirituality Informing Public Policy : Joseph Wresinski and Our Understanding of Extreme Poverty - Wodon, Quentin (Taylor and Francis, 2018)
The understanding of the relationship between human rights and extreme poverty at the United Nations owes much to Joseph Wresinski, the founder of the International Movement ATD Fourth World. While Wresinski was a Catholic priest, he deliberately created an inter-denominational organization and developed a unique spirituality rooted in a shared life experience with the extreme poor. He considered that spirituality, broadly understood, should be at the heart of the fight against extreme poverty and social exclusion. He hoped that his message could be heard by men and women from all faiths who are concerned about the plight of the extreme poor.